High glycated albumin is an independent predictor of low response to clopidogrel in ACS patients: a cross-sectional study - Xiliang Zhao (Cardiovascular Diabetology, 2020)
Abstract Background Glycated albumin (GA) is a marker of short-term glycemic control and is strongly associated with the occurrence of diabetes. Previous studies have shown an association between GA and the effect of clopidogrel therapy on ischemic stroke. However, limited information is available regarding this relationship in acute coronary syndrome (ACS) patients. In this study, we evaluated the effect of GA on platelet P2Y12 inhibition by clopidogrel in patients with ACS. Methods Consecutive Chinese patients with ACS who received loading or maintenance doses of clopidogrel in addition to aspirin were recruited. At least 12 h after the patient had taken the clopidogrel dose, thromboelastography (TEG) and light transmittance aggregometry (LTA) were used to calculate the quantitative platelet inhibition rate to determine clopidogrel-induced antiplatelet reactivity. A prespecified cutoff of the maximum amplitude of adenosine diphosphate (ADP)-induced platelet-fibrin clot strength > 47 mm plus an ADP-induced platelet inhibition rate < 50% assessed by TEG or ADP-induced platelet aggregation > 40% assessed by LTA to indicate low responsiveness to clopidogrel were applied for evaluation. Patients were categorized into two groups based on a GA level of 15.5%, the cutoff point indicating the development of early-phase diabetes. Multivariate linear regression analysis was used to assess the interaction of GA with clopidogrel antiplatelet therapy. Results A total of 1021 participants were evaluated, and 28.3% of patients (289 of 1021) had low responsiveness to clopidogrel assessed by TEG. In patients with elevated GA levels, low responsiveness to clopidogrel assessed by TEG was observed in 33.7% (139 of 412) of patients, which was a significantly higher rate than that in the lower-GA-level group (24.6%, P = 0.002). According to multivariate linear regression analysis, a GA level > 15.5% was independently associated with low responsiveness to clopidogrel after adjustment for age, sex and other conventional confounding factors. This interaction was not mediated by a history of diabetes mellitus. A GA level ≤ 15.5% was associated with a high positive value [75.4%, 95% CI 73.0–77.6%] for predicting a normal responsiveness to clopidogrel. Conclusions GA could be a potential biomarker to predict the effects of clopidogrel antiplatelet therapy in ACS patients and might be a clinical biomarker to guide DAPT de-escalation.